A novel l-rhamnose-binding lectin participates in defending against bacterial infection in zebrafish. Issue 134 (March 2023) - Wang, Jing; Guo, Xin-Lu; Chen, Hong-Ye; Xiao, Lin-Xi; Yang, Gui-Wen; Yang, Hui-Ting
Abstract: l -rhamnose-binding lectin (RBL), which is a class of animal lectins independent of Ca 2+, can specifically bind l -rhamnose or d -galactose. Although several lectins in zebrafish have been reported, their functional mechanisms have not been fully uncovered. In this study, we discovered a novel l -rhamnose binding lectin ( Dr RBL) and studied its innate immune function. The Dr RBL protein contains only one carbohydrate-recognition domain (CRD), which includes two strictly conserved motifs, "YGR" and "DPC". Dr RBL was detected in all tested tissues and was present at high levels in the spleen, hepatopancreas and skin. After Aeromonas hydrophila challenge, the Dr RBL mRNA level was significantly upregulated. Additionally, Dr RBL was secreted into the extracellular matrix. Recombinant Dr RBL (r Dr RBL) could significantly inhibit the growth of gram-positive/negative bacteria, bind to several bacteria and cause obvious agglutination. The r Dr RBL protein could combine with polysaccharides, such as PGN and LPS, rather than LTA. A more detailed study showed that r Dr RBL could combine with monosaccharides, such as mannose, rhamnose and glucose, which are important components of PGN and LPS. However, r Dr RBL could not bind to ribitol, which is an important component of LTA. The Dr RBL deletion mutants, Dr RBL Δ144-150 and Dr RBL Δ198-200, were also constructed. Dr RBL Δ144-150 ("ANYGRTD" deficient) showed weak bacterial inhibiting ability. However, Dr RBL Δ198-200 ("DPC" deficient) showed weak agglutination ability. These results suggest that the "DPC" domain is important for agglutination. The conserved domain "ANYGRTD" is essential for inhibiting bacterial growth. Highlights: Dr RBL participates in defending against bacteria in zebrafish. Dr RBL could partially bind monosaccharides in a specific manner. The "DPC" domain plays a more important role in resisting bacterial growth. The "ANYGRTD" domain is necessary for agglutinating bacteria.